Application and adaptation of Symphonology Bioethical Theory (SBT) in pastoral care practice - Khechane, M. M. (HTS teologiese studies, 2008)
In an environment which is ethically and from a human rights point of view overly sensitive and in which interculturism is becoming more and more a norm, pastoral care practitioners need to be committed to providing services that are ethical, intercultural and respecting of patients’ rights. This article demonstrates how application of the Symphonology Bioethical Theory (SBT) as the framework for practice in pastoral care and counselling can help Pastoral Care Practitioners (PCP) to be ethical while upholding patients’ human rights, and it can also help to bridge the intercultural chasm while simultaneously explaining the rationale for the practice. Symphonology is a context-driven, ethical decision- making model guiding holistic interaction between patients and PCPs. The Symphonological decision-making matrix is based on a practitioner-patient agreement for pastoral care that emphasizes patient preferences, pastoral psychological and theological knowledge, the pastoral care content and the context of the situation. The goal of the PCP is to ethically incarnate the divine presence and thus to bring about hope and emancipation to the patient using the bioethical standards of autonomy, freedom, objectivity, self-assertion, benevolence and fidelity.